Missed Opportunities of Simplification Regarding Personal Income Tax Systems in Hungary - Szabóné Bonifert, Éva (Public Finance Quarterly, 2021)
The paper investigates – considering also the simplified basic elements of the current system – the possibilities of simplifying the Hungarian personal income tax system’s composition in the previous years, while tax burden curves of the system change as little as possible. Tax burden curves of the theoretical, simplified tax model established for this investigation are fitted to the curves of the real tax system, while the parameters of the theoretical model are determined by a computer program. Since the modern Hungarian income taxation had been introduced, the system has long been subject to a wide variety of changes concerning the basic elements examined in the study. Selecting some of these years of changes, the study analyses the possibilities for simplification in order to ask the question again: whether it is necessary to maintain complex tax systems at all costs, possibly in favour of achieving the most equitable income tax system. The results of the investigation indicate that our simpler theoretical system could have replaced with a good approximation the elements of Hungarian tax systems of previous years with multi-bracket and sometimes complicated tax credit, which even applied more tax benefit elements compared to the theoretical system. On this basis, it may be an important aspect also for the more distant future that in the course of developing personal income tax systems, the sophisticated equity of the systems should be observed through the mathematical spectacles of simplification options.